Mechanical and tribological properties of B-C-N coatings sliding against different wood balls - Wu Zhiwei; Wang Yan; Li Sihao; Wang Xiaoyong; Xu Zhaojun; Zhou Fei (Science and Engineering of Composite Materials, 2019)
BCN coatings with different chemical compositions were prepared using RF magnetron sputtering via adjusting N2 flow. The influence of N2 flow on the bonding structure, mechanical and tribological properties of coating was studied. The structural analysis indicated the coexistence of B-N, B-C, and N-C bonds, suggesting the formation of a ternary BCN hybridization. The maximum Vickers hardness of 1614.7 HV was obtained at the low N2 flow (5 sccm), whereas the adhesion strength of BCN coatings on 316L stainless steel was improved with an increase of N2 flow. The friction behavior of BCN coatings sliding against different materials (acerbic, beech and lauan wood) was performed using ball-on-disk tribo-meter in air. The low friction coefficient was easier to obtain as sliding against hardwood i.e. acerbic balls. BCN-5 and BCN-10 coatings presented better wear resistance regardless of softwood or hardwood, whilst other two coatings were more suitable for mating softwood i.e. beech and lauan.